Efficacy of Preplant and Early Postemergence Herbicides in Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several herbicide treatments applied sequentially for weed control in irrigated corn. Acuron (metolachlor + atrazine + mesotrione + bicyclopyrone), Clarity (dicamba), Corvus (isoxaflutole + thiencarbazone), Halex GT (metolachlor + glyphosate + mesotrione), and Lumax EZ (metolachlor + atrazine + mesotrione) were compared when combined at various ratios and timings. All combinations gave similar levels of weed control, allowing a producer to compare these tank mixes head-to-head based on prices alone.
Keywords: Residual control; sequential applications